The Analysis Of Translation Methods For The Labels Of Eight Statue Collections At The Singhasari Museum - Yubitasya Pratiwi; Hanif Rizky (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2026)
A museum is a place for cultural preservation that aims to preserve and store objects of cultural and historical heritage. A museum also conveys information about culture and history to the public. The Singhasari Museum is an archaeology and history museum that preserves and displays artifacts about the Singasari Kingdom. The Singhasari Museum has eight collections of statues from heritage sites of Singasari Kingdom. This research aims to examine the translation methods used to provide the collection labels of the eight statues preserved at the Singhasari Museum, namely: Bhairawa statue, Durga Mahisasuramardini statue, Ganesha standing statue, Ganesha sitting statue, Nandi statue, Nandiswara statue, Mahisha statue, and Mahakala statue. The researcher conducted research with a qualitative descriptive approach. This research produces data in the form of written analysis to identify the translation methods used to translate eight statue labels in Singhasari Museum based on Peter Newmark’s translation method (1988). The results of the current research indicate that the translator predominantly applied source-text-oriented translation methods. The analysis of the data indicates that the faithful translation method was the most frequently and dominantly used to translate the label of eight statue collections preserved in the Singhasari Museum